Electrochemical detection of small molecule induced Pseudomonas aeruginosa biofilm dispersion. (1st April 2018) - Robb, Alex J.; Vinogradov, Sergey; Danell, Allison S.; Anderson, Eric; Blackledge, Meghan S.; Melander, Christian; Hvastkovs, Eli G.
Abstract: A simple electrochemical assay to monitor the dispersion of Pseudomonas aeruginosa PA01 biofilm is described. Pyrolytic graphite (PG) electrodes were modified with P. aeruginosa PA01 using layer-by-layer (LbL) methods. The presence of the bacteria on the electrodes was directly monitored using square wave voltammetry (SWV) via the electrochemical reduction of electroactive phenazine compounds expressed by the bacteria, which indicate the presence of biofilm. Upon treatment of bacteria-modified electrodes with a 2-aminoimidazole (2-AI) derivative with known Pseudomonas anti-biofilm properties, the bacteria-related electrochemical reduction peaks decreased in a concentration dependent manner, indicating dispersal of the biofilm on the electrode surface. A similar 2-AI compound with negligible anti-biofilm activity was used as a comparative control and produced muted electrochemical results. Electrochemical responses mirrored previously established bioassay-derived half maximal inhibition concentration (IC50 ) and half maximal effective concentration (EC50 ) values. Biofilm dispersal detection via the electrochemical response was validated by monitoring crystal violet absorbance after its release from electrode confined P. aeruginosa biofilm. Mass spectrometry data showing multiple redox-active phenazine compounds are presented to provide insight into the surface reaction complexity. Overall, we present a very simple assay to monitor the anti-biofilm activity of compounds of interest. Graphical abstract: